The impact of left ventricular size on outcomes after centrifugal-flow left ventricular assist device implantation. (11th November 2021) - Molina, Ezequiel; Jain, Amiti; Ahmed, Sara; Lam, Phillip; Rao, Sriram; Hockstein, Michael; Kadakkal, Ajay; Hofmeyer, Mark; Rodrigo, Maria; Chou, JiLing; Najjar, Samer; Sheikh, Farooq
Abstract: OBJECTIVES: The influence of preoperative left ventricular size in outcomes following centrifugal-flow left ventricular assist device (LVAD) implantation has not been well characterized. METHODS: A cohort of 313 patients who received a centrifugal-flow LVAD at a single institution was analysed. Using a maximally selected log-rank statistic, we investigated whether a left ventricular end-diastolic dimension (LVEDD) cut-off point was associated with worse outcomes. The cohort was then divided in 2 groups based on the LVEDD cut-off point. RESULTS: An LVEDD cut-off point of 59 mm was found to predict worse survival. Smaller LVEDD patients (≤59 mm, N = 52) were older and more likely to have a history of coronary artery disease compared those with a larger LVEDD (>59 mm, N = 261). Smaller LVEDD patients had lower survival compared to larger LVEDD patients (71% vs 85% at 1 year and 58% vs 80% at 2 years, P = 0.003). The need for temporary right ventricular mechanical support was significantly higher in the smaller LVEDD cohort (11.5% vs 1.9%, P = 0.002). Pump flows at time of discharge were lower in the smaller LVEDD group (3.8 vs 4.2 l/min, P = 0.005), who also had a higher incidence of late right ventricular failure (23% vs 12%, P = 0.02), higher rates of gastrointestinal bleeding (0.416 vs 0.256 events per patient-year, P = 0.025) and higher readmissions secondary to low flow alarms (0.429 vs 0.240 events per patient-year, P = 0.007). Multivariable analysis demonstrated that smaller LVEDD, older age, high BUN and high bilirubin levels were independent predictors of worse survival. CONCLUSIONS: In patients receiving a centrifugal-flow LVAD, smaller preoperative LVEDD (≤59 mm) was associated with lower survival and higher incidence of adverse outcomes. Abstract : As survival continues to improve and the incidence of adverse events is slowly ameliorating, left ventricular assist device (LVAD) therapy is increasingly being embraced for the treatment of stage D heart failure patients [1].